2018
DOI: 10.18321/ectj694
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of Graphene Coated Nickel Foam as an Anode for Lithium-Ion Battery

Abstract: This study reports the synthesis of a few-layered graphene (GF) thin film on Ni foam by chemical vapor deposition (CVD) technique and investigation of its electrochemical performance as a negative electrode for lithium-ion batteries (LIBs). A standard deposition procedure with a methane precursor was employed to prepare the GF films. The SEM studies revealed the formation of a dark uniform film on the surface of Ni foam’s wires upon the CVD deposition. The film consisted of numerous GF sheets replicating the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…1), and the latter is related to further delithiation of Li (x-y) Si to amorphous Si (a-Si) at higher potential (Eq. 2): 30,31…”
Section: Resultsmentioning
confidence: 99%
“…1), and the latter is related to further delithiation of Li (x-y) Si to amorphous Si (a-Si) at higher potential (Eq. 2): 30,31…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Mukanova et al 41 reported graphene (GF) thin film on NiO‐Ni foam by CVD technique and investigated its electrochemical performance as anode for LIBs. The 3D GF coated NiO‐Ni anode exhibited a gradual increase of its areal charge capacity from 65 μAh cm −2 at the initial cycle to 250 μAh cm −2 at the final 250th cycle.…”
Section: Binder Free Porous Nio‐ni Foam As Anode Of Libsmentioning
confidence: 99%